Preventing well leg compartment syndrome among patients in the lithotomy position-Operating room nurses' perspectives: A qualitative study - Johansson Susanne; Hörnsten Åsa (Wiley, 2023)
Abstract Aim To describe operating room nurses' experiences of well leg compartment syndrome and how they work perioperative to prevent it during the lithotomy position. Design The study had a qualitative design. Methods Focus group interviews were performed with 10 operating room (OR) nurses. The interviews were semi‐structured and analysed by qualitative content analysis. The study complied with the Consolidated Criteria for Reporting Qualitative Research (COREQ). Results The main theme showed that the OR nurses shoulder duty and responsibility, independently and in the team, but they need more structural support and knowledge. The themes showed that they follow routines whenever possible and take responsibility for positioning; however, they have to balance between flexibility and strict routines. Although they also develop and participate in teamwork, they still need further knowledge. Conclusion The severe complication of well leg compartment syndrome (WLCS) can occur when the patient is in the lithotomy position. Maintaining the same routines and paying attention to the WHO's surgical safety checklist were described as actions that could prevent well leg compartment syndrome. Patient or Public Contribution No patient or public contribution. We have interviewed nurses but without financial support since the study was performed and supervised within a master programme.